Piling Tool Graph Set / Noraisyah Mohamad … [et al.] - Mohamad, Noraisyah; Hussin, Juliyana; Abd Rahman, Mohd Fazli; Mat, Mazziyatol Farizza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Piling Tool Graph is created to reduce problem that emerges in the construction place. Problem which arise here was the risk when the labourer taking the graph during the piling which set in the soil by manual method. With "Piling Tool Graph Set" this problem could be overcome and it is able to reduced risk and increased the safety of the labourer during in construction site. The labourer can use this machine by placed the machine near to the pile and attached the pencil to the pile that can draw the graph during the piling, then the machine can be moved by used remote control to control the pencil movement in far distance. So that, the graph will be accurate. So by use this Piling Tool Graph Set, we have advantages and also can reduced the risk while the piling work was conducted.